Broad‐spectrum health improvements with one year of soccer training in inactive mildly hypertensive middle‐aged women. (25th January 2017) - Krustrup, P.; Skoradal, M.‐B.; Randers, M. B.; Weihe, P.; Uth, J.; Mortensen, J.; Mohr, M.
Abstract : The study tested the hypothesis that long‐term soccer training has positive impact on cardiovascular profile, body composition, bone health, and physical capacity in inactive, pre‐menopausal women with mild hypertension. The study applied a randomized controlled design in which physically inactive middle‐aged women were separated into a soccer training group (n=19; SOC) and a control group (n=12; CON). SOC performed 128±29 (±SD) one‐h small‐sided soccer training sessions over one year. Blood pressure, body composition, blood lipid profile, and fitness level were determined pre‐ and post‐intervention. Over one year, mean arterial pressure decreased more in SOC than in CON (−5±7 vs +4±5 mmHg; P <.05). Total‐body fat mass decreased more ( P <.05) in SOC than in CON (−2.5±2.5 vs +0.6±3.2 kg; P <.05), while the change scores for lean body mass were not significantly different in SOC (2.6±2.7 kg) compared to CON (1.1±1.9 kg, P =.09). Over one year, change scores in whole‐body bone mineral density (0.004±0.032 vs −0.019±0.026 g·cm 2 ) as well as bone mineral content (30±70 vs −39±113 g) were positive in SOC compared to CON ( P <.05). Post‐intervention plasma triglycerides decreased more (−0.1±0.7 vs +0.2±0.2 mmol·L −1 ) and HDL cholesterol increased more (0.2±0.7 vs −0.2±0.2 mmol·L −1 ) in SOC than in CON ( P <.05). Yo‐Yo intermittent endurance level 1 (122±105 vs 2±21%) and 20‐m sprint performance (6±6 vs −1±2%) increased more ( P <.05) in SOC than in CON. In conclusion, long‐term soccer training resulted in broad‐spectrum improvements in the health profile of untrained, pre‐menopausal women with mild hypertension, including cardiovascular, metabolic, and musculo‐skeletal benefits.